Cost of Nursing Care and The Role of Nurse Manager - Handan Alan (Association of Nurse Managers, 2018)
Medical professionals' compassion for the trauma and pain that patients experience, developing empathy and prolonged exposure to the traumas experienced by patients lead to compassion fatigue. Nursing is one of the professions experiencing severe compassion fatigue. There are a lot of psychical emotional/psychological and social symptoms of compassion fatigue among nurses. Caregiving willingness, skills and energy of nurses who experience a compassion fatigue in nurses. That is increases medical mistakes, and decrease on patient satisfaction, and leave job among nurses. for reason, nurse managers should give due importance to it, and programs for avoiding and treatment of compassion fatigue should be created. In this essay, nurse manager's role on compassion fatigue; definition, effects and importance of it on nursing care has been discussed in order to increase awareness about compassion fatigue and its effects which is experienced by nurse managers.